Research on the Application of Nanomaterials in Textile Field - Chai, keyi (International Journal of Materials Science and Technology Studies, 2025)
Nanomaterials, due to their unique properties, have shown great potential in the textile industry, significantly enhancing functionality, comfort, and intelligence. However, their application still faces technical challenges and safety concerns. This study reviews the significant applications of nanomaterials in textiles, emphasizing that through technological innovation and standardization, nanotextiles can achieve more efficient functionality and environmental friendliness, bringing greater convenience to human life. Future research should focus on developing multifunctional textiles, establishing standards, and improving safety evaluation systems to promote the healthy development of the textile industry.